Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's solve the given system of equations step by step. The system is:
[tex]\[ \begin{cases} 3a + b = 2 \quad \text{(Equation 1)} \\ 9a^2 - b = 7 \quad \text{(Equation 2)} \end{cases} \][/tex]
### Step 1: Express [tex]\( b \)[/tex] from Equation 1
From Equation 1, we can isolate [tex]\( b \)[/tex]:
[tex]\[ b = 2 - 3a \][/tex]
### Step 2: Substitute [tex]\( b \)[/tex] into Equation 2
Now, we substitute [tex]\( b = 2 - 3a \)[/tex] into Equation 2:
[tex]\[ 9a^2 - (2 - 3a) = 7 \][/tex]
### Step 3: Simplify the resulting equation
Simplify the left-hand side:
[tex]\[ 9a^2 - 2 + 3a = 7 \][/tex]
Move all terms to one side to form a standard quadratic equation:
[tex]\[ 9a^2 + 3a - 9 = 0 \][/tex]
Divide the entire equation by 3 to simplify:
[tex]\[ 3a^2 + a - 3 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve the quadratic equation [tex]\( 3a^2 + a - 3 = 0 \)[/tex], we use the quadratic formula:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 3 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = -3 \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = 1^2 - 4 \cdot 3 \cdot (-3) = 1 + 36 = 37 \][/tex]
[tex]\[ a = \frac{-1 \pm \sqrt{37}}{6} \][/tex]
So we get the solutions:
[tex]\[ a_1 = \frac{-1 + \sqrt{37}}{6} \][/tex]
[tex]\[ a_2 = \frac{-1 - \sqrt{37}}{6} \][/tex]
### Step 5: Find corresponding [tex]\( b \)[/tex] values
Using [tex]\( b = 2 - 3a \)[/tex], we substitute [tex]\( a_1 \)[/tex] and [tex]\( a_2 \)[/tex]:
For [tex]\( a_1 = \frac{-1 + \sqrt{37}}{6} \)[/tex]:
[tex]\[ b_1 = 2 - 3 \left( \frac{-1 + \sqrt{37}}{6} \right) = \frac{12 - 3(-1 + \sqrt{37})}{6} = \frac{12 + 3 - 3\sqrt{37}}{6} = \frac{15 - 3\sqrt{37}}{6} = \frac{5 - \sqrt{37}}{2} \][/tex]
For [tex]\( a_2 = \frac{-1 - \sqrt{37}}{6} \)[/tex]:
[tex]\[ b_2 = 2 - 3 \left( \frac{-1 - \sqrt{37}}{6} \right) = \frac{12 - 3(-1 - \sqrt{37})}{6} = \frac{12 + 3 + 3\sqrt{37}}{6} = \frac{15 + 3\sqrt{37}}{6} = \frac{5 + \sqrt{37}}{2} \][/tex]
### Conclusion
The solutions to the system of equations are:
[tex]\[ \left(a, b\right) = \left( \frac{-1 + \sqrt{37}}{6}, \frac{5 - \sqrt{37}}{2} \right) \][/tex]
and
[tex]\[ \left(a, b\right) = \left( \frac{-1 - \sqrt{37}}{6}, \frac{5 + \sqrt{37}}{2} \right) \][/tex]
Thus, the solutions are:
[tex]\[ \left( \frac{-1 + \sqrt{37}}{6}, \frac{5 - \sqrt{37}}{2} \right) \quad \text{and} \quad \left( \frac{-1 - \sqrt{37}}{6}, \frac{5 + \sqrt{37}}{2} \right) \][/tex]
[tex]\[ \begin{cases} 3a + b = 2 \quad \text{(Equation 1)} \\ 9a^2 - b = 7 \quad \text{(Equation 2)} \end{cases} \][/tex]
### Step 1: Express [tex]\( b \)[/tex] from Equation 1
From Equation 1, we can isolate [tex]\( b \)[/tex]:
[tex]\[ b = 2 - 3a \][/tex]
### Step 2: Substitute [tex]\( b \)[/tex] into Equation 2
Now, we substitute [tex]\( b = 2 - 3a \)[/tex] into Equation 2:
[tex]\[ 9a^2 - (2 - 3a) = 7 \][/tex]
### Step 3: Simplify the resulting equation
Simplify the left-hand side:
[tex]\[ 9a^2 - 2 + 3a = 7 \][/tex]
Move all terms to one side to form a standard quadratic equation:
[tex]\[ 9a^2 + 3a - 9 = 0 \][/tex]
Divide the entire equation by 3 to simplify:
[tex]\[ 3a^2 + a - 3 = 0 \][/tex]
### Step 4: Solve the quadratic equation
To solve the quadratic equation [tex]\( 3a^2 + a - 3 = 0 \)[/tex], we use the quadratic formula:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 3 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = -3 \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = 1^2 - 4 \cdot 3 \cdot (-3) = 1 + 36 = 37 \][/tex]
[tex]\[ a = \frac{-1 \pm \sqrt{37}}{6} \][/tex]
So we get the solutions:
[tex]\[ a_1 = \frac{-1 + \sqrt{37}}{6} \][/tex]
[tex]\[ a_2 = \frac{-1 - \sqrt{37}}{6} \][/tex]
### Step 5: Find corresponding [tex]\( b \)[/tex] values
Using [tex]\( b = 2 - 3a \)[/tex], we substitute [tex]\( a_1 \)[/tex] and [tex]\( a_2 \)[/tex]:
For [tex]\( a_1 = \frac{-1 + \sqrt{37}}{6} \)[/tex]:
[tex]\[ b_1 = 2 - 3 \left( \frac{-1 + \sqrt{37}}{6} \right) = \frac{12 - 3(-1 + \sqrt{37})}{6} = \frac{12 + 3 - 3\sqrt{37}}{6} = \frac{15 - 3\sqrt{37}}{6} = \frac{5 - \sqrt{37}}{2} \][/tex]
For [tex]\( a_2 = \frac{-1 - \sqrt{37}}{6} \)[/tex]:
[tex]\[ b_2 = 2 - 3 \left( \frac{-1 - \sqrt{37}}{6} \right) = \frac{12 - 3(-1 - \sqrt{37})}{6} = \frac{12 + 3 + 3\sqrt{37}}{6} = \frac{15 + 3\sqrt{37}}{6} = \frac{5 + \sqrt{37}}{2} \][/tex]
### Conclusion
The solutions to the system of equations are:
[tex]\[ \left(a, b\right) = \left( \frac{-1 + \sqrt{37}}{6}, \frac{5 - \sqrt{37}}{2} \right) \][/tex]
and
[tex]\[ \left(a, b\right) = \left( \frac{-1 - \sqrt{37}}{6}, \frac{5 + \sqrt{37}}{2} \right) \][/tex]
Thus, the solutions are:
[tex]\[ \left( \frac{-1 + \sqrt{37}}{6}, \frac{5 - \sqrt{37}}{2} \right) \quad \text{and} \quad \left( \frac{-1 - \sqrt{37}}{6}, \frac{5 + \sqrt{37}}{2} \right) \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.